Contribution to the knowledge of Atyidae and Palaemonidae (Crustacea: Decapoda) of Greece - Kapakos, Yiannis; Karaouzas, Ioannis (Zootaxa, 2019)
This contribution aims in enhancing knowledge of the zoogeography of the freshwater shrimp fauna of Greece, based on field collections carried out from 2002–2016. A total of 167 specimens were collected from 25 locations in rivers, streams and lakes of the Greek peninsula and islands. Our study adds more localities with exclusive records of A. acheronensis/A. desmarestii in central- western Greece, where it was previously presumed that A. stankoi occurred. Furthermore, A. stankoi is now recorded for the first time in two rivers of eastern central Greece, as well as in a spring system of western Greece, being thus its westernmost record so far.